Genomic insights from Paraclostridium bifermentans HD0315_2: General features and pathogenic potential - Zhao, Hailan; Wang, Jiaqi; Peng, Yao; Cai, Xunchao; Liu, Yandi; Huang, Wenqi; Huang, Hongli; Nie, Yuqiang (Frontiers in Microbiology, 2022)
Background: Paraclostridium bifermentans is the most diverse distributed species of Paraclostridium and can cause fatal human infections under rare conditions. However, its pathogenic mechanisms and adaptation ability behind infections remain unclear. Herein, we reported the complete genome sequence of P. bifermentans HD0315_2 isolated from the feces of a Crohn’s disease patient. Then, we performed genomic analyses to understand its pathogenic mechanisms and adaptation ability. Results: The de novo assembly revealed that the HD0315_2 strain carried a circular chromosome of 3.27 Mb and six circular plasmids (19.41 to 139.50 kb). The phylogenomic analysis assigned the HD0315_2 strain as P. bifermentans and reclassified some previously non-P. bifermentans strains into this clade. The general genomic features showed that this species harbored a flexible genomic pool characterized by variable genome length and multiple plasmids. Then, the HD0315_2 strain was predicted as a human pathogen with high probability, and Listeria LIPI-1 virulence proteins were identified on its genome. Besides, abundant antibiotics/metal/stress resistant genes, such as asrABCH, cat, mccF, macB, entS, albA, bcrA and tetB, were carried by either the genome or the plasmids. Furthermore, we proposed that transposase-directed horizontal gene transfer was responsible for the distribution of multiple copies of the hin gene in the plasmids. Conclusion: The flexible genomic pool of P. bifermentans encodes abundant functions for antimicrobial or oxidative stress resistance, helping it successfully inhabit and adapt to diverse environments. Moreover, P. bifermentans HD0315_2 might infect hosts via a Listeria LIPI-1-like cycle, with the help of a plasmid expressing the Hin DNA invertase to evade host immune responses.